Isolation, Characterization, and Identification of Biosurfactant-Production Bacteria from Used Cooking Oil Waste - Pratama, Fisky Aditya; Dewi, Pramesti; Mubarok, Ibnul; Mustikaningtyas, Dewi (Universitas Muhammadiyah Surakarta, 2025)
Waste cooking oil constitutes a significant environmental concern in Indonesia. It has the potential to be utilized as a substrate for biosurfactant-producing bacteria. Biosurfactants are amphiphilic compounds produced by microorganisms, containing both hydrophilic and hydrophobic components that enable them to dissolve in both water and fats, as well as to reduce surface tension. This study aims to isolate, characterize, and identify biosurfactant-producing bacteria from waste cooking oil. Isolation proccess was conducted using Mineral Salt Medium enriched with cooking oil as an inducer and Carboxy Methyl Cellulose as a carbon source and emulsifier. Two isolates were successfully obtained and purified. Their biosurfactant-producing ability was evaluated through drop collapse test and oil spreading test. One isolate demonstrated superior performance, showing positive activity in both tests, including a 0.7 cm oil spreading zone. Identification involved macroscopic observation, Gram staining, endospore staining, and a catalase test. The isolate exhibited characteristics of a Gram-positive, rod-shaped, spore-forming, catalase-positive bacterium with small, circular, milky-white colonies and a smooth surface. This identification is non-molecular and based on a phenotypic approach according to Bergey’s Manual for preliminary bacterial classification. Based on these features, the isolate is presumed to belong to the genus Bacillus, known for its robust biosurfactant production. The findings suggest that waste cooking oil can be a promising source of indigenous biosurfactant-producing bacteria, contributing to both microbial conservation and potential development of eco-friendly biotechnological products.